Respuesta :
2x - y + 3z= 10 --------> equation 1
-3x + y - 2z= -11 --------> equation 2
-4x + y - 4z = -15 --------> equation 3
Add first and second equation
2x - y + 3z= 10
-3x + y - 2z= -11
---------------------------
-x + z = -1 -----------------> equation 4
Add first and third equation
2x - y + 3z= 10
-4x + y - 4z = -15
---------------------------
-2x - z = -5 -----------------> equation 5
Now add equation 4 and 5
-x + z = -1
-2x - z = -5
-----------------
-3x = -6
Divide both sides by -3
so x= 2
We use equation 4 and solve for z
-x + z = -1
-2 + z = -1
Add 2 on both sides
z = 1
Now plug in x=2 and z=1 in any one of the original equation
2x - y + 3z= 10
2(2) - y + 3(1)= 10
4 - y +3 = 10
7 - y = 10
subtract 7 on both sides
-y = 3
y = -3
x=2, y=-3, z= 1
Solution is (2,-3, 1)
solve by linear combination
use 1st equation to cancel y's in 2nd and 3rd equations
add 1st equation to 2nd equation to get
-x+z=-1
add 1st equation to 3rd equation to get
-2x-z=-5
now add the 2 new equations -x+z=-1 and -2x-z=-5 to get
-3x=-6
x=2
sub back
-x+z=-1
-2+z=-1
z=1
sub back
-3x+y-2z=-11
-3(2)+y-2(1)=-11
-6+y-2=-11
y=-3
(x,y,z)=(2,-3,1)
C is answer